2012
DOI: 10.1016/j.febslet.2012.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate homeostasis in the yeast Saccharomyces cerevisiae, the key role of the SPX domain‐containing proteins

Abstract: a b s t r a c tIn the yeast Saccharomyces cerevisiae, a working model for nutrient homeostasis in eukaryotes, inorganic phosphate (Pi) homeostasis is regulated by the PHO pathway, a set of phosphate starvation induced genes, acting to optimize Pi uptake and utilization. Among these, a subset of proteins containing the SPX domain has been shown to be key regulators of Pi homeostasis. In this review, we summarize the recent progresses in elucidating the mechanisms controlling Pi homeostasis in yeast, focusing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 66 publications
(123 reference statements)
2
130
0
Order By: Relevance
“…The identification of evolutionarily conserved homology sequences defining specific 'domains' and their architecture in proteins through bioinformatics has become the de facto standard in protein analysis, providing hints on protein functions. One of these conserved regions, the SPX domain (Pfam: PF03105; see Glossary), named after the yeast proteins Syg1 and Pho81 and the mammalian Xpr1, has emerged in the past decade as a key region/signature of proteins involved in regulating aspects of phosphate metabolism [7].…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of evolutionarily conserved homology sequences defining specific 'domains' and their architecture in proteins through bioinformatics has become the de facto standard in protein analysis, providing hints on protein functions. One of these conserved regions, the SPX domain (Pfam: PF03105; see Glossary), named after the yeast proteins Syg1 and Pho81 and the mammalian Xpr1, has emerged in the past decade as a key region/signature of proteins involved in regulating aspects of phosphate metabolism [7].…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
“…However, only the recent acquisition of the crystal structure of several SPX domains [35] allows us to appreciate how this region reads the phosphate cellular status. The sequences defining the SPX domain are of variable length, ranging from 135 to >400 amino acids [7], resulting in a tripartite organization with three distinct homology regions of 30-40 amino acids ( Figure 2). The resolved SPX structures revealed that the first homology region is normally organised into two small helices (1 and 2) while the two other homologous regions form long helices (3 and 4) that constitute the core of the structure.…”
Section: Spx Structure Reveals a Thought-provoking Inositol Polyphospmentioning
confidence: 99%
“…The availability of Pi in rhizosphere or PAS might be sensed in G. margarita by VIP1 and Pho81 genes, whose transcript levels are induced in the symbiotic mycelia grown under Pi-limiting conditions and are repressed in the presence of abundant Pi ( Table 1 and Figure 7). It is predicted that intracellular VIP1 and Pho81 proteins transmit the Pi signal downstream of the PHO pathway under low-Pi conditions, and presumed interaction of Pho81 with IP7 and complex Pho80-Pho85 ( Lee et al, 2008 andSecco et al, 2012) permits the nuclear localization of the transcription factor NUC-1, thus activating the PHO-responsive genes (Table 1). In contrast, under normal or excess Pi conditions, expression levels of VIP1 and Pho81 genes are reduced more, the levels of Pho81 protein could decrease in AM fungi, and the active ternary complex Pho81-Pho80-Pho85 may phosphorylate NUC-1 to sequestrate it in the cytoplasm.…”
Section: Conservation Of Pho and Pka Pathways In Am Fungi And Dual Romentioning
confidence: 99%
“…Phosphate acquisition, storage, and metabolism in fungi have been best studied with Saccharomyces cerevisiae and Neurospora crassa (14)(15)(16)(17). The high-affinity phosphate uptake system in S. cerevisiae consists of Pho84, which mediates proton-coupled cotransport, and Pho89, which performs sodium-coupled transport upon phosphate limitation (18)(19)(20).…”
mentioning
confidence: 99%